A apropriação da língua inglesa pelo aluno cego matriculado no ensino fundamental : um estudo de caso - Perinni, Sanandreia Torezani (2013)
This research aimed to understand the ways of appropriation of the English language by blind student enrolled in the common rooms of elementary education in the regular school system. For the development of this research I chose to take a qualitative approach in the context of the case study building on the theoretical and philosophical assumptions of socio-historical approach, based on the contributions of Vygotsky, Bakhtin and authors who share this line. The research had as subject of study a visually impaired student, the English teacher and teacher specializing in specialized educational services. The corpus of the research was obtained from document analysis, semi-structured interviews, observation of English classes and the school environment. Data analysis showed that learning the blind student does not differentiate regarding the learning of other students, just needs other ways to perform as well as the fact that disability is realized only in the interactions in the social environment. The data also show that the school is aware of the differences in school life, however, with regard to the actions curriculum within the classroom, I found a little flexible curriculum to the needs of students with and without disabilities, a practice teaching that still favours the explanation of content, exercises and writing reviews, and mostly individual. Whereas the meaning of disability is the result of the combination of the history of the individual with the social environment, the data collected indicate that the acquisition of knowledge in the English language by blind student arise amid difficulties ranging from the lack of suitable materials to the senses attributed by the subjects of this process about visual impairment, specifically blindness, in other words, the challenges that exist in this process are determined in the social context and not on biological characteristics.